Insulin‐like growth factor binding protein‐4 inhibits cell growth, migration and invasion, and downregulates COX‐2 expression in A549 lung cancer cells. (21st February 2017) - Li, Weiwen; Sun, Debin; Lv, Zhuqing; Wei, Yueqiu; Zheng, Liyun; Zeng, Tingting; Zhao, Jialu
Abstract: Insulin‐like growth factor binding protein 4 (IGFBP‐4) and cyclooxygenase2 (COX‐2) are associated with tumor inflammatory microenvironment which is involved in the progression of tumor. However, it is unclear that the roles of IGFBP‐4 in lung cancer and the effects of IGFBP‐4 on COX‐2 expression. In this study, we showed that IGFBP‐4 could decrease COX‐2 production in lung cancer A549 cells. IGFBP‐4 expression was significantly lower but COX‐2 expression was higher in lung cancer tissues compared to matched adjacent normal tissues. In addition, IGFBP‐4 could inhibit lung cancer cell proliferation, migration and invasion, and suppress the phosphorylation of PI3 K/AKT, ERK, and CREB. These results indicate that IGFBP‐4 has potent antitumor effects in non‐small cell lung cancer cells.